Drillability machine and hopper at the Agricultural Engineering Laboratory (1955)
General view of the drillability machine at the U.S. Department of Agriculture's Agricultural Engineering Laboratory showing the distribution of wet granular fertilizer as deposited by the Grether hopper.
Keywords: Nitrogen fertilizer industry; United States. Bureau of Chemistry and Soils; Fertilizer industry--Equipment and supplies; United States. Department of Agriculture; Machinery